Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have two equations:

\begin{align*} 3 \ln x + \ln y &= 3 \\ 4 \ln x - 6 \ln y &= -7 \\ \end{align*}

Do I just proceed as I have learned with adding equations resulting in:

\begin{align*} 18 \ln x + 6 \ln y &= 18 \\ 4 \ln x - 6 \ln y &= -7 \\ 22 \ln x &= 11 \\ \end{align*}

Then solve from there?

share|cite|improve this question
Yes, that is exactly what you do. I assume that going from $22\ln x =11$ to $x=e^{1/2}$ is obvious for you. However, the way you express your calculation will almost certainly lose you marks. For example, $18\ln x +6\ln y=18$. – André Nicolas Dec 13 '11 at 16:30
Thanks, that answered my question exactly. Your correction is the way it's written down, I just made the error here on the site. – erimar77 Dec 13 '11 at 16:33
up vote 3 down vote accepted

Yes, that is how the system is handled. In a more complicated situation, we might want to make a substitution, letting $u=\ln x$ and $v=\ln y$. Then our two equations become $$3u +v=3, \qquad 4u-6v=-7.$$ This is a system of two linear equations in the two unknowns $u$ and $v$.

If we have a system of quite a few linear equations in quite a few unknowns, we need to adopt a systematic approach. For our simple system, almost anything sensible will work. For example, we can try to "eliminate" $v$ (that was your strategy). Multiply each side of the first equation by $6$. We obtain $18u+3v=18$.

From the equations $18u+3v=18$ and $4u-6v=-7$, we obtain, by adding, that $22u=11$, so $u=1/2$. Substituting this in one of the equations, we get $v=3/2$.

So $\ln x=1/2$ and $\ln y=3/2$. It follows that $x=e^{1/2}$ and $y=e^{3/2}$.

Comment: As noted above, for this simple system almost any reasonable strategy will work. For example, in high school one might be encouraged to rewrite the first equation as $v=3-3u$, and then substitute for $v$ in the second equation. We would get $$4u-6(3-3u)=-7,$$ which, after some manipulation, yields $22u=11$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.